Young people, procedural justice and police legitimacy in Nigeria - Akinlabi, Oluwagbenga (2017)
Most findings from developed western societies – particularly USA and UK – have consistently found that young people's judgement about police legitimacy is built predominantly on procedural justice. Empirical investigations to test this assertion among youth from developing and less cohesive societies remain scarce. This article explores the possibility of closing this gap in literature. It assesses the strength of procedural justice effect in comparison with other police behaviour and inherent characteristics of young people in Nigeria. Using data collected from six secondary schools in Nigeria, the results substantiate the procedural justice hypothesis in the West; confirming that procedural justice is a more important predictor of police legitimacy than police effectiveness. The study also confirm that police legitimacy is further associated with other variables included in the analysis. The implications of these current findings are discussed